The Relationship between Total Cholesterol Level with Incidence of Stroke on Patient Who Treated at dr. M. Yunus Hospital Bengkulu - Devi Listiana; Awal Isgiyanto; Mezi Ade Saputra (Jurnal Sains Kesehatan, 2018)
The number of stroke patients in Indonesia from year to year continues to increase. Stroke in Indonesia is the number three killer after infectious disease and coronary jatung. The purpose of this study is to determine Relationship of Total Cholesterol level with Incidence of Stroke on Patients who treated at inpatient ward Dr. M. Yunus Hospital Bengkulu. This study used survey analytic design with cross sectional method. Population in this study were all stroke patients who treated at Inpatient Ward Dr. M. Yunus Hospital Bengkulu in 2016 with the amount of 355 people who contain of 138 haemoragic stroke and 217 people with non haemorragic stroke. Sample in this study was 78 people who contain of 30 people patients with haemorragic stroke and 48 people with non haemorragic stroke obtained with proporsional simple random sampling technique. Collecting data in this study used secondary data who obtained from medical record at Inpatient Ward Dr. M. Yunus Hospital Bengkulu. The results of this study : there were 48 people (61,5%)  with non haemorragic stroke; there were 36 people (46,2%)  with high cholesterol levels, and there is significant relationship between total cholesterol level with Incidence of Stroke on patients who treated at Inpatient Ward Dr. M. Yunus Hospital Bengkulu with moderate category relationship. It was expected that health workers in Stroke Inpatient Room of RSUD M. Yunus Bengkulu especially nurses in order to provide more complete nursing care, especially in stroke patients. Keywords: cholesterol levels, patient, stroke